THE IMPLEMENTATION OF WRITE-PAIR-SHARE TECHNIQUE IN TEACHING WRITING PROCEDURE TEXT TO THE TENTH GRADE STUDENTS OF SMAN 1 KEDIRI (RETAIN, 2014)
THE IMPLEMENTATION OF WRITE-PAIR-SHARE TECHNIQUE IN TEACHING WRITING PROCEDURE TEXT TO THE TENTH GRADE STUDENTS OF SMAN 1 KEDIRI Muhammad Baiqun Isbahi English Education Department, Language and Art Faculty, Surabaya State University. email : baiqunbai@gmail.com Drs. Fahri, M.A. English Education Department, Language and Art Faculty, Surabaya State University. Abstrak Penelitian ini bertujuan untuk mendeskipsikan penerapan teknik Write-Pair-Share untuk mengajar menulis teks procedure pada siswa kelas sepuluh di SMAN 1 Kediri, untuk mendeskripsikan penerapan teknik Write-Pair-Share untuk mengajar menulis teks procedure, dan untuk mendeskripsikan hasil menulis teks procedure siswa setelah penerapan teknik Write-Pair-Share untuk mengajar menulis teks procedure. Penelitian ini menggunakan penel itian deskriptif qualitative tanpa ada perhitungan statistik. Hasil penelitian ini menunjukkan bahwa teknik Write-Pair-Share sukses diterapkan di kelas dan teknik yang membantu baik guru dan siswa dalam proses belajar mengajar menulis teks procedure dalam konteks „knowledge of content, organization, vocabulary, language use, and mechanics‟. Teknik Write-Pair-Share mampu mengaj ak minat siswa untuk menulis. Kata Kunci: Menul is, teknik Write-Pair-Share, teks procedure, siswa kelas sepuluh Abstract This study is conducted to describe the implementation of Write-Pair-Share technique in teaching writing procedure text to the tenth grade students of SMAN 1 Kediri, describe the implementation of Write-Pair-Share technique in teaching writing procedure text, and the students result after the implementation of Write-Pair-Share technique in teaching writing procedure text. This study used descriptive qualitative research without any statistical calculation. The result of this study showed that Write-Pair-Share technique was successfully implemented in class and it was helpful technique for both the teacher and the students in teaching and learning process of writing procedure text in terms of „knowledge of content, organization, vocabulary, language use, and mechanics‟. Write-Pair-Share technique could engage the students‟ willingness to write. Keywords: Writing, Write-Pair-Share technique, procedure text, tenth grade students are composition, in which the teachers ask the students to write a composition based on the material or teaching topic individually. First is jigsaw technique, in which the students have to make a group of several students, then write a composition together and the leader of the group should teach the other members in order to make all of the group members understand with their composition, because the teacher will call one of them randomly to explain in front of the class (Kagan, 2001). Second is Numbered Heads Together (Kagan, 2001) stated that a class is divided into several groups which consists of four students in each group. In every student in a group is given numbers of 1, 2, 3, and 4. The groups work together with the each member of the group, and the teacher will call out a number (one), so the students who have number three have to answer the teacher‟s question. Third is Write-Pair-Share (WPS) technique which has similarity with writing stages, and many other techniques. Those techniques above focus on writing activity, which help both teachers and students in teaching learning writing. By using those techniques, teachers are easy to engage the students‟ willingness to write and the students will have more willingness to write. Among those techniques above, Write-Pair-Share (WPS) technique is the focus in this study. As an alternative technique which engages students‟ willingness to write, this Write-Pair-Share technique is an appropriate technique to be applied in teaching writing skill since the stages in this technique are the same as the common stages in writing skill. For example, the first stage of this technique, that is writing down the ideas individually is the same as planning stage. The second stage of this technique, that is discussing the ideas with pair is similar with drafting stage, while sharing the result with the other pairs to get more feedback is the same as revising stage. Besides, the researcher also thinks that Write-Pair-Share technique which belongs to cooperative learning can help the students in teaching learning process. Moreover, eighth grade students are included in adolescent learners who are bound up need for peer approval like cooperative learning (Harmer, 2007:83). Cooperative Learning (CL) itself is an approach which organizes classroom activities by grouping the students to do the activities together for improving students‟ understanding of a subject (Jacobs et.al, 2003). In this study the researcher focuses on the implementation of Write-Pair-Share technique in teaching writing procedure text because the researcher believes that the students can write procedure text easily using this technique which has some stages in writing process. In writing procedure text, the students can write their experiences or events in the past. Based on SI (Standar Isi) or Competence Based Curriculum, procedure itself is one of text types (genres) which how to do something which contains goal, materials, and steps. The researcher believes that by using Write-Pair-Share technique, it can help the students more enthusiastic in writing procedure text. Here, the researcher will investigate more about the implementation of Write-Pair-Share technique in teaching writing procedure text, and the students writing procedure text task when Write-Pair-Share technique is applied. Based on the background above, the researcher‟s big expectation of this research is therefore to reveal the implementation of Write-Pair-Share technique in teaching procedure text by conducting this research to the tenth graders of SMAN 1 Kediri. Related to the reasons above, the foundations of the study are come up to the surface as the research questions. Those are: How does the teacher implement Write-Pair-Share technique in teaching writing procedure text to the tenth grade students of SMAN 1 Kediri? How are the students procedure writing text result during the implementation of Write-Pair-Share technique in teaching writing procedure text? This study is conducted to describe the implementation of Write-Pair-Share technique in teaching writing procedure text to the tenth grade students of SMAN 1 Kediri, and the students result after the implementation of Write-Pair-Share technique in teaching writing procedure text. Writing is one of the productive skills in the form of written text which needs more accuracy than speaking because we cannot correct ourselves as soon as possible like correcting speaking (Harmer, 2012:128). Compared to speaking skill, writing skill considers many aspects that need to be regarded. They are content, organization, vocabulary, language use, and mechanic. Because when we make mistakes during speaking, we can correct it directly and other people can tolerate us. On the other hand, when we make mistakes during writing, we cannot correct it directly and people cannot tolerate it. Moreover, writing skill can involve the students‟ meaning-focused use, language focused-use, and fluency development (Nation. 2009: 113). Therefore, the students have to be more accurate in writing. There are some statements related to writing process. First, Boas (2011) says that writing is one of the English skills whose activity is planning, drafting, and revising texts. Second, Hedge (1993) argues that the process of writing are pre-writing, while-writing, and post-writing. Meanwhile, O‟Malley & Pierce (1996:254) say that there are three stages in writing process, they are pre-writing, drafting, and post-writing. And other expert explains there are four stages in writing process; they are planning, drafting, editing, and final version (Harmer, 2012: 128-129). In this study the researcher will use Harmer‟s concept. Planning Planning stage is the first stage which leads the students to write. In this stage, the students will plan what they want to write. It will stimulate them to find their ideas to write. Boas (2011) says that planning stage is used for brainstorming ideas which are related to their lives and what they want to write. Drafting In this stage, the students can start to write what they want to write after planning their ideas. Here, the students just write their ideas in to the draft without thinking the neatness of their writing. Editing After making draft, the students review their rough draft and edit it before they write their final version. The students check their rough draft, whether it is perfect or not and they can add their ideas if it is necessary. In this case, the students can check the content, grammar, vocabulary, and so on. After editing, they can continue to the next stage that is final version. Final version In the last stage, the students still have chance to rethink what they have written and go back to editing stage or even planning stage. Because Harmer (2012:129) states that writing stages are like writing cycle, if it is necessary to add ideas or edit their writing, we can go back to the previous stage or stages. But if it does not need to edit, the students can do their writing final version. The purpose of all processes in writing; planning, drafting, editing, and final version is to improve students‟ writing ability. By those processes above, the students will try to make a good paragraph or essay. In teaching learning process, cooperative learning is needed because the students can share their ideas and knowledge during writing with their friends in their group. It has a chance to increase the students confidence in sharing their opinion in their group (Harmer, 2007:166). Write-Pair-Share (WPS) technique is one of the cooperative learning techniques which is adapted from Think-Pair-Share. The steps in Write-Pair-Share technique are writing down the ideas individually (Jacobs et.al, 1997:13). It means that the students cannot do the first step together with the pair or other friends, they have to write down the ideas individually. Then discussing the ideas with the pair or partner who consists of two students. Here the students can ask, give advice to the pair or partner before sharing to other groups. Then the last step is sharing their writing result in front of the class to get feedback from other groups in class (Jacobs et al, 1997:20). The other groups can correct and give advice to their friends‟ mistakes. Write-Pair-Share technique is one of the techniques which the teacher used in teaching writing procedure text. Although Write-Pair-Share technique is not too efficient because of some stages there, this technique helps the students to develop conceptual understanding of a topic, the students‟ ability to draw conclusions, and the students‟ ability to consider their friends‟ point of view (Kagan and Kagan, 1994:89). Because of certain time during implementing of Write-Pair-Share technique, the writing activity becomes more focused than usual. The students can write and discuss their composition with their partner or their friend on time (Kagan, 1994). The implementation of Write-Pair-Share technique in teaching writing procedure text should include writing process, they are planning, drafting, editing, and final version (Harmer, 2012:129). Based on Harmer‟s concept, the implementation of Write-Pair-Share technique in teaching writing procedure text in the class have some activities to do. They are: The teacher explains and gives example of procedure text. The teacher also explains how to write mind- mapping. The teacher gives a topic to write procedure text. The teacher asks the students to write down the students‟ planning in mind mapping. The teacher asks the students to exchange their work with their partner. The students can write their procedure text draft. The teacher calls one of the students randomly to share the draft in front of the class. The students submit their procedure text result as the final version to the teacher. METHODS This study is concerned with describing the implementation of Write-Pair-Share technique in teaching writing procedure text. Therefore, this study used descriptive qualitative research. The purpose of this study is to describe the teaching learning process in the form of words not in the form of numbers, because this study is descriptive qualitative. Moreover, Bogdan and Biklen (1992:28) state that the data collected should be in the form of words or pictures rather than numbers. The data in this study will be described in the form of words, sentences, or paragraphs to describe the implementation, the students‟ responses, and the students procedure writing text result using Write-Pair-Share technique in teaching writing procedure text. The subjects of this study are the teacher and the students in SMAN 1 Kediri. The researcher chooses one of three English teachers in SMAN 1 Kediri, who teaches in X-1 class and he is used to use cooperative learning in his class. The researcher believes that he can implement Write-Pair-Share technique in his class easily. The researcher chooses the tenth grade students in SMAN 1 Kediri as the subjects of this study. The researcher chooses this grade, because according to Competence Based curriculum, tenth grade students have to write text types such as procedure, descriptive, and procedure text in writing skill. The researcher also thinks that they have gotten English since they were in Elementary school; they just explore and improve their ability in writing skill. Cohen, et al (2007:461) states that descriptive qualitative focuses on smaller numbers of people than quantitative research. Therefore, the researcher only chooses one class in SMAN 1 Kediri, that is X-1 which contains 34 students because the students. The observation of this study would be at SMAN 1 Kediri. The setting of the study would be conducted in room X-1 of SMAN 1 Kediri. There are 15 males‟ students and 19 females‟ students who sit on 34 chairs and use 17 desks. Each student sits in one single chair and writes on double desk. Referring to the research questions in Chapter 1, the researcher would take data and sources of the data of this study. For the first research question, the data are teachers activity during the implementation of WritePair-Share technique in teaching writing procedure text, start from the beginning until the end of the class. To get these data, the researcher observed the teacher during the implementation of Write-Pair-Share technique in teaching writing procedure text. Meanwhile, for the second research question, the data are words, phrases, and sentences from the students procedure writing text result. To get these data, the researcher analyzed the students procedure writing text result by using ESL Composition profile. Research instruments used to analyze the data in this study are: (1) Observation checklist, (2) Field note, (3) Students procedure writing text result. Technique used to collect the data in this study is observation. Since the design of this study is descriptive qualitative research, the researcher here acts as a nonparticipant observer. In other words, the researcher observed the teacher when he was conducting teaching learning process and fill the observation checklist. Besides, the researcher also took a note on all the activities in teaching learning process to support the data in observation checklist. Then the researcher spread out questionnaire to the students at the last meeting. At last, the researcher collecting and analyzing the students‟ procedure writing text using ESL composition profile. After collecting all of the data which were gotten from the observation checklist, field note, and students procedure writing text, the researcher then analyzed them descriptively. The data were gotten from the teacher through observation checklist and field note. The result of observation checklist and field note was used to compile the information about the teachers implementation of Write-Pair-Share technique in teaching writing procedure text and the problems occur during the implementation. Besides from the teacher, Meanwhile, the data gathered from the students procedure writing text result gave information whether the technique is applicable and understandable or not in writing procedure text. RESULT AND DISCUSSION Result The researcher did the research for three days on Friday March 3rd, Wednesday March 10th , and Friday May 17th 2014. The researcher here is as an observer who sat at the backward of the class. The researcher observed the implementation of Write-Pair-Share technique in teaching writing procedure text, the students‟ responses after the implementation of Write-Pair-Share technique in teaching writing procedure text, and the result of the students‟ procedure writing text. 1. The First Meeting The first observation was conducted on Friday, March 3rd 2014. The class began at 09.40 a.m., the teacher had already prepared the teaching materials. All of the students were ready in their desk but few of them were outside the class after taking a rest. The captain of the class called his friends that the lesson had begun. The teacher started the class by greeting the students, checking the attendance, and reviewing the teaching material. There were thirty six students in this class, but two of them had to move to the other school because of some matters. As a result, there were only thirty four students but today three of them were sick. The teacher reviewed procedure text, some of them asked why they had to reviewed it again, because they had learned procedure text at the beginning of the semester. T : “Ok let‟s continue the lesson, who still remember about procedure text?, raise your hand.” S : “Lho kok procedure text lagi Sir, kan sudah diajarkan dulu.” S : “Kenapa diulang lagi Sir?” T : “Iya sekarang beda menulis procedure text menggunakan Write-Pair-Share technique or WPS technique.” S : “Apa itu?” T : “WPS technique itu teknik menulis yang harus menulis ide awal kalian dalam bentuk mind mapping, trus diskusi dengan teman sebangku kalian, setelah itu baru di diskusikan bersama didepan kelas” S : “Waduh angele ae Sir Sir”. S : “Mind mapping itu yg buat gambar bulet-bulet itu ya Sir?” T : “Good, lho who can answer my question about procedure text?” S : “procedure text kan yang step-step kan?” T : “Very good, then the generic structure?” S : “goal and materials”. T : “And then?” S : “steps Sir”. T : “What are the language features of procedure text?” S : “Use present tense”. T : “Why?” S : “Because urutannya Sir”. Then, the teacher gave a handout which consist of another example of procedure text and asked the students to answer the exercises. Almost of the students could do the exercises correctly. The teacher also told the students about Write-Pair-Share in general before the time was over. The teacher closed the class by greeting the students and concluding the material. 2. The Second Meeting The second meeting was conducted on Wednesday March 10th 2014. The class began at 8.20 a.m., the teacher had prepared all the materials and the media, such as laptop and LCD projector. Today all the students attended the class. The teacher began the class by greeting the students, checking the attendance, and reviewing the last meeting about procedure text and Write-Pair-Share technique. Most of the students had still confused about Write-Pair-Share technique. The teacher explained more about Write-Pair-Share technique. The teacher asked the students to write procedure text with the topic which teacher divided using Write-Pair-Share technique. The students had to write different topic with their friends, one topic only for three or four students. At first, the teacher asked the students to write down their ideas into mind mapping for ten minutes. Ten minutes letter, the teacher asked the students to discuss and share their mind mapping and make a draft from that mind mapping with their pair. After that, the students stopped to make a draft and the teacher called a student to share the draft in front of the class using LCD projector. At first, the students did not know what they have to do in share stage. T : “This is your friend‟s draft, now you can give advice or comment of this draft.” S : “Maksudnya apa sir? I don‟t understand”. T : “Silent please, maksudnya itu tulisan teman kalian, mbak Wulan harus kalian komentari dari tensesnya, besar kecil tulisan, titik komanya, isi ceritanya juga betul apa salah. Now wulan it‟s your turn”. There were only two students who shared the draft in front of the class and the other students also had a chance to revise their draft based on sharing stage. The teacher closed the class by concluding the activity, asking the students to bring dictionary in the next meeting , and greeting the students. 3. The Third Meeting It was on Friday, March 17th 2014, The class began at 09.40 a.m., the teacher had prepared the teaching material and the media, like laptop and LCD projector. There were two students who were sick today. The teacher began the class by greeting the students, checking the attendance, and reviewing the material in the last meeting. The teacher explained Write-Pair-Share technique again and explained the students‟ mistake in the first task. T : “Students pay attention please, do you still remember about procedure text?” S : “Yes Sir I remember.” T : “Very good, if you still remember, I will ask you what tenses we use in writing procedure text? Tenses apa yang kita gunakan dalam menulis procedure text” S : “Simple present tense Sir.” T : “Nah itu harus sering-sering buka kamus. Dan ada beberapa yang salah penulisan conjunction after that tapi ditulis after dad. Today, the students had still to write procedure text using Write-Pair-Share technique, but different topic. The teacher asked the students to write procedure text based on their own experiences. The stages were same with stages in the first task, wrote down the ideas in the form of mind mapping, shared with their pair to make a draft from their mind mapping, and shared in front of the class. But in the middle of the lesson, the electricity was off, so the students had to write the draft in the white board. The students did all stages quietly, because they understood what they do using Write-Pair-Share technique and they brought dictionaries. The teacher closed the class by concluding the lesson, and greeting the students. Then, the researcher asked the students to fill the questionnaire that given by the researcher for a while before the students went home. The Result of Students’ Procedure Writing Text To describe the students procedure writing text, the researcher described it through the students‟ writing scores for each component from content, organization, vocabulary, language use, and mechanics. In this part, the researcher explained the students procedure writing text that is used to answer the third research question in Chapter 1. The researcher used Jacobs, H, et al. (1981) ESL composition profile which had four writing criteria. They are, very good, good, fair, and poor. After analyzing the students procedure writing text using ESL composition profile, the researcher did not forget to discuss the students score with the teacher. . Discussion The discussion explains the result of the implementation of Write-Pair-Share technique in teaching writing procedure text, the students‟ responses after the implementation of Write-Pair-Share technique in teaching writing procedure text, and the result of the students‟ procedure writing text. The Implementation of Write-Pair-Share Technique Based on the result of three meetings on May 3rd, 8th, and 10th 2013, it could be seen that the implementation of Write-Pair-Share technique helped the students to develop their topic (Kagan and Kagan, 1994:89). The implementation was appropriate with Jacob, et al. (1997:13) that the students have to write down the ideas individually, discuss the ideas with the pair, and share the result with the other pairs. At the first meeting on March 3rd 2014, in preparation step the teacher reviewed procedure text by giving handout which consists of example of procedure text and some exercises. The teacher only reviewed procedure text, because the students had learned about procedure text at the beginning of the semester and the teacher explained Write-Pair-Share technique in general. After that, the teacher and the students analyzed the example of procedure text together. The teacher also did not forget to ask the students to make question if they still did not understand with the example. Then the teacher continued the lesson by asking the students to do the exercises. Almost of the students could answer the exercises correctly. At the second meeting on May 8th 2014, the teacher also did not forget to remind the students about procedure text. In this meeting, the teacher asked the students to write procedure text using Write-Pair-Share technique with different topic that teacher gave. In the write stage, the teacher asked the students to write their ideas into mind mapping for ten minutes (Jacobs et.al. 1997:13). The teacher gave the students an example how to make mind mapping on the whiteboard. And then in pair stage, the teacher asked them to share and discuss with their partner about their mind mapping and continued their mind mapping into the draft for about twenty minutes. In that stage, some students had difficulties in using verb and vocabularies. Thirty minutes later, the teacher asked the students to share their draft in front of the class. The teacher called one of them randomly to share their draft in front of the class. After sharing stage, the teacher gave the students more time to edit and revise their draft based on the sharing stage before submitting the final version. At the third meeting on May 10th 2013, the teacher asked the students to write procedure text freely based on their experiences. Before the teacher asked the students, he gave feedback for the first task in the second meeting, because feedback is important in writing activity (Nation, 2008). Although using different topic, but the technique was same with the second meeting that is using WritePair-Share technique. The students‟ writing ability was getting better than the second meeting, because the students had a chance to discuss and get comment or suggestion from their partner (Jacobs et.al, 1997:14), they also brought their own dictionary. By using WritePair-Share technique, the students could be more focus in writing procedure text than usual (Kagan, 2004) The Students’ Procedure Writing Text There are five components in writing; they are content, organization, vocabulary, language use, and mechanics. Here the teacher only asked the students to submit the final version of the students‟ recount writing text result, which consists of students‟ mind mapping and students‟ recount writing text result without the students‟ recount writing text rough draft. Therefore, the researcher only analyzed the students‟ recount writing text result according to Jacobs, H, et al. (1981) ESL composition profile based on recount text. The teacher saw the students‟ progress from the general score of the students‟ recount writing text result from the first task and the second task. Before the researcher analyzed it, the students had passed planning, drafting, editing, and final version (Harmer, 2012:128-129). Based on the students‟ recount writing result, the researcher presents the result of the content analysis on the students‟ writing recount text from the first and the second task. It was used to simplify and to know the students‟ improvement in content term. In the first task there were five students who got good criteria and seven students who got very good level. It means that they could focus on developing their ideas related to the topic and the story was knowledgeable. Then there were five students got good criteria in the first task and there were two students got good level in the second task, in this criteria, the students presented limited development of story and lack detail of specific participants. Meanwhile, the students who considered as fair criteria were five students the first task and nine students in the second task. It means that the students in this criteria had limited knowledge of specific participants and inadequate development ideas related to the topic. And the students who categorized into poor criteria had decreased, from seventeen students in the first task, became eleven students in the second task. The students‟ organization became better by using Write-Pair-Share technique. There were some students who could develop their writing in organization. From four students who got very good level in the first task, became eight students who got very good level in the second task. It means that the students who got very good level could organize the generic structure of recount text (Orientation, events, and re-orientation) and the students had fluent expression, ideas clearly supporting sentences. And the poor level was decrease from eighteen students in the first task became fourteen students in the second task. It means that the students had known their mistakes in organizing the text and in connecting each sentence. From the explanation above, it could be seen that the students‟ ability in term of organization were successfully enhanced by using Write-Pair-Share technique. In vocabulary component, there were two students who considered as very good criteria in the first task and three students who considered as very good criteria in the second task. The students in this criteria were increased, it means that they used word choice and usage, temporal conjunction and temporal circumstances, material (or action) processes, and relational (or mental) processes correctly. Next, there were six students who got good criteria in the first task and nine students in the second task. Then three students in the first task and eight students in the second task who considered as fair criteria. Meanwhile, seventeen students got poor criteria in the first task became ten students in the second task. It means the students in this criteria used essential translation, did not use temporal conjunctions and temporal circumstances. It could be concluded that the students‟ ability in terms of vocabulary were successfully enhanced by using Write-Pair-Share technique. Based on the data presented, language use is one of the components in writing that is little bit difficult to improve. For example in the first task, there were only one student who was categorized into very good level, and there were two students who were categorized into very good level in the second task. It means that the students had few errors use of past tense, word order or function, pronouns, and prepositions. In the first task there were four students who got good level and six students in the second task. In this criteria, the students had several errors use of past tense, word order or function, pronouns, prepositions but the meaning seldom obscured. While in the first task and in the second task, only four students who got fair criteria. The students had still frequent errors use of past tense, word order or function, pronouns, prepositions, meaning confused or obscured. Meanwhile, there were twenty students in the first task and there were eighteen students in the second task. It showed not too significant development in language use term. Dealing with the result of the mechanics analysis of the students‟ recount writing text, it also showed not too significant development in mechanics term. Because, there were two students who were considered as very good criteria in the first task and there were four students who were considered as very good criteria. In this criteria, the students had few errors of spelling, punctuation, capitalization, paragraphing. There were eight students in the first task and there were six students in the second task who categorized as good criteria. It means that the students were occasional errors of spelling, punctuation, capitalization, paragraphing but the meaning was not obscured. Meanwhile, in fair criteria, there were five students in the first task and there were seven students in the second task. And the last, there were thirteen students in the first task who got poor criteria and there were thirteen students in the second task. It could be concluded that there were little progress in term of mechanics. CONCLUSION AND SUGGESTION Conclusion In this study, there are three conclusions got from the result of the study that are obtained from the observation in SMAN 1 Kediri They are described as follows: Write-Pair-Share technique can be used as teaching technique in teaching writing recount text to the eighth grade students of SMAN 1 Kediri. The implementation of Write-Pair-Share technique in teaching writing of procedure text can be divided into three sections, those are: - Write stage, it includes planning stage where the students had to write down their ideas in the form of mind mapping. - Pair Stage , it includes drafting stage where the students developed their mind mapping to be procedure text draft with their pair. The students were allowed to discuss with their pair; they could give comments and suggestions to each other. - Share stage, it includes editing and final version of writing procedure text. The students had to share their draft in front of the class; their friends could give comments, suggestions, and feedback from the teacher if it is necessary. Then the students had to edit and submit the final version of their procedure text. The researcher used structured questionnaire to know the students‟ responses toward the teaching of writing procedure text by using Write-Pair-Share technique. Based on the result of questionnaire, most of the students were interested in using Write-PairShare technique as teaching technique in teaching writing procedure text. Because, the students had a chance to discuss and get comment or suggestion from their partner (Jacobs et.al, 1997:14). The use of Write-Pair-Share technique could help the eighth grade students of SMPN 1 Tarik in learning writing procedure text. It is shown by the result of the students‟ procedure writing text. They were asked to write a procedure text based on the theme and their own experience. And most of the students could write procedure text using Write-Pair-Share technique, because the students could be more focus in writing procedure text than usual (Kagan, 2004). It is provided from the students‟ score which improves from the first task to the second task. Suggestion Based on the data interpretation and the previous conclusion, the researcher has some suggestions to the teachers and the other researcher. The researcher constructs her suggestions as follows: In teaching young learners, the teacher should know and understand their characteristics because they have different characteristics from the adults. The English teachers have to be creative in teaching learning process especially in teaching writing. It means that the teachers should use the teaching technique or material so that it can avoid the students‟ boredom and make them interested in learning to write. The researcher would like to invite next researchers who conduct the similar study to make improvement on this study, such as using the same field but different subjects. It means they can use the other subjects. REFERENCES Ary, D, et al. 2010. Introduction to Research in Education. USA: Wadsworth, Cengage Learning. Boas, V. I. 2011. Process Writing and the Internet: Blogs and Ning Networks in the Classroom. English Teaching Forum. 49(2),. 1-8. Bogdan, R.C. and Biklen,S.K. 1992. Qualitative Research for Education:An Introduction to Theories and Methods. Boston:Pearson. Brown, H. Douglas. 2004. Language Assessment: Principles and Language Classroom Practices. White Plains, New York: Pearson Education. Brown, H. Douglas. 2007. Teaching by Principles, An Interactive Approach to Language Pedagogy. United States of America: Longman. Cohen, L, et al. 2000. Research Methods in Education. London: RoutledgeFalmer. Cohen, L, et al. 2007. Research Methods in Education. London: RoutledgeFalmer. Depdiknas.2004.Kompetensi Mata Pelajaran Bahasa Inggris untuk SMP dan MTS. Jakarta: Depdiknas. Habibah, Nur Laela. 2012. The Effectiveness of Write‑ Pair-Share Technique to Teach Writing Narrative Text to the Eleventh Graders of SMA Negeri 3 Kediri. Unpublished Thesis S-1. Surabaya: Universitas Negeri Surabaya. Harmer, Jeremy. 2001. The Practice of English Language Teaching. London: Longman. Harmer, Jeremy. 2007. The Practice of English Language Teaching. London: Longman. Harmer, Jeremy. 2012. Teacher Knowledge. London: Longman. Hedge, T. 1993. Writing. Oxford: Oxford University Press. Jacobs, G. M, et al. 2003. Using cooperative learning in large classes. http://www.georgejacobs. net/ retrieved on February 18th 2013. Jacobs, George M, et al.1997. Learning Cooperative Learning Via Cooperative Learning: A Sourcesbook of Lesson Plans For Teach Education